Mekanisme Fitur Wakaf pada Produk Asuransi Jiwa Syariah PT Allianz Life Indonesia - Azhar Alam Sukri Hidayati (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2021)
This study describes the waqf features of AlliSya Protection Plus Unit Link Endowments on Sharia Life Insurance Investment products at PT Asuransi Allianz Life Indonesia. This type of research uses field research (field literature) and literature (library research) with a qualitative approach that is descriptive as well as analyzing data with the analysis description method. The results of the study show the fact that the waqf feature starts with the waqf application and promise procedure and involves the waqf agency. This study also revealed a large percentage of insurance benefits that can be donated a maximum of 45% and a potential benefit of a maximum investment value of 30% into waqf institution. Running waqf features on Islamic life insurance products is an increase in increasing the collection of endowment funds, thereby increasing both the welfare of society and economic development.